Die invloed van versteurde inlaatvloeipatrone op aksiaalwaaiers - Visser, J. G. J. (Stellenbosch : Stellenbosch University, 2012)
Stellenbosch University. Faculty of Engineering. Dept. of Mechanical and Mechatronic Engineering.